Foamed ceramics prepared by rare earth blast furnace slag and fly ash and preparation method thereof

By optimizing the ratio of rare earth blast furnace slag and fly ash, adding waste glass and talc powder, and using coal gangue and silicon carbide as foaming agents, the problems of low utilization rate of fly ash solid waste and uneven pores in the prior art were solved, and foamed ceramics with high compressive strength and low cost were prepared.

CN119349989BActive Publication Date: 2025-04-01BAOGANG GRP METALLURGICAL SLAG COMPREHENSIVE UTILIZATION & DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411947784.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

In the prior art, when using blast furnace slag and fly ash to prepare foamed ceramics, there are problems such as low utilization of fly ash solid waste, excessive types of additives, high cost of foaming agents, low compressive strength of the product and uneven pores.

Method used

By optimizing the raw material ratio of rare earth blast furnace slag and fly ash, adding solid waste resources such as waste glass and talc powder, and using coal gangue and a small amount of silicon carbide as foaming agents, foamed ceramics are prepared by direct foaming sintering.

Benefits of technology

The utilization rate of rare earth blast furnace slag and fly ash was improved, and foamed ceramics with excellent performance were prepared, with high compressive strength, uniform pore distribution and low-cost process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349989B_ABST
    Figure CN119349989B_ABST
Patent Text Reader

Abstract

The present application provides a foamed ceramic prepared by rare earth blast furnace slag and fly ash and a preparation method thereof. The foamed ceramic of the present application is fired with rare earth blast furnace slag, fly ash, crushed silica, coal gangue, waste glass, talcum powder, and silicon carbide as raw materials. The raw materials of the foamed ceramic of the present application are rich in sources, and the rare earth blast furnace slag and fly ash account for more than 50% of the raw materials, which improves the utilization rate of rare earth blast furnace slag and fly ash. Not only the rare earth blast furnace slag and fly ash are effectively treated at the same time, but also the high value-added resource utilization of solid wastes such as coal gangue and crushed silica is realized. In addition, the foamed ceramic of the present application also has the characteristics of high compressive strength, low area density, and low water absorption. The method of the present application adopts a direct foaming and sintering method to prepare foamed ceramics, which improves the sintering performance of rare earth blast furnace slag, reduces the cost of foaming and sintering, shortens the process flow, and the production link is green and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of resource utilization of solid waste, and in particular to a foamed ceramic prepared by using rare earth blast furnace slag and fly ash, and a preparation method thereof. Background Art

[0002] As a wall insulation material, foamed ceramics have the advantages of light weight, sound insulation, high strength, and environmental protection. Compared with traditional organic insulation materials, they have obvious advantages in high temperature resistance and durability. The use of industrial solid waste to prepare foamed ceramic materials not only complies with the energy conservation and emission reduction policy advocated by the country, but also can make resource utilization of waste residues to obtain high value-added material products. Therefore, the use of industrial waste residues to prepare foamed ceramic materials has become a hot topic in current research.

[0003] Coal gangue, fly ash and rare earth blast furnace slag are all industrial solid waste resources with large production quantities and low utilization rates in Inner Mongolia.

[0004] Coal gangue is a solid waste generated during coal mining and washing. It is mainly composed of carbonaceous, muddy and sandy shale. It has a low calorific value and a carbon content of 20%-30%. It also contains a certain proportion of Al 2 O 3 (aluminum oxide) and SiO 2 (Silicon dioxide), but due to its 30%-40% ignition loss when burned at high temperatures and its own low economic value, it is often regarded as an industrial waste.

[0005] Rare earth blast furnace slag is a solid waste produced during the blast furnace ironmaking process and is a type of solid waste in the metallurgical industry. Rare earth blast furnace slag has been used as a raw material for low value-added products such as cement and engineering backfill, which not only wastes the sensible heat of the slag, but also creates very limited social and economic benefits. Rare earth blast furnace slag contains a large amount of CaO, SiO 2 , MgO and Al 2 O 3 As well as trace amounts of rare earth elements, the main crystal phase exists in the form of glass phase, pyroxene phase and pyroxene phase, which is suitable for the preparation of SiO 2 -Al 2 O 3 -CaO system is the basic chemical composition of foamed ceramic materials. However, the melting temperature of rare earth blast furnace slag is relatively high, exceeding 1550°C, which has a great influence on the sintering temperature and sintering time of foamed ceramics.

[0006] Fly ash is the fine fly ash and bottom slag obtained from the flue gas of coal-fired power plants and power plants that comprehensively utilize coal sludge resources after being collected by dust collectors. Fly ash in Inner Mongolia contains rich SiO 2 and Al 2 O 3The sum of the two is more than 70%, which mainly exists in the form of mullite, quartz, aluminosilicate glass, etc., and has the ability to prepare SiO 2 -Al 2 O 3 The chemical composition of the system foamed ceramics. However, due to the complex mineral phase, uneven component distribution and volatility of the fly ash raw material itself, the pores generated inside the product vary greatly, especially the uniformity of the pore size distribution is difficult to ensure, which often leads to poor product performance.

[0007] The Chinese patent with publication number CN108503371A discloses a method for preparing foamed ceramic materials using blast furnace slag and high-aluminum fly ash, wherein blast furnace slag, high-aluminum fly ash and silica sand are used as raw materials, borax, sodium metaphosphate and clay are used as flux and foam stabilizer, sodium carbonate and calcium carbonate are selected as foaming agents, the temperature is raised to 1100~1200℃ in a medium temperature furnace, and the temperature is kept for 50~90min to obtain a formed foamed ceramic with a volume density of 0.447g / cm 3 , compressive strength is 1.87MPa, and thermal conductivity is 0.1W / (m·K). Although this method obtains foamed ceramic materials by foaming and sintering blast furnace slag and fly ash, there are problems such as low fly ash solid waste utilization rate, too many types of additives, high foaming agent cost, low product compressive strength, and uneven pores.

[0008] Therefore, there is an urgent need for a reasonable design of the ratio of rare earth blast furnace slag and fly ash raw materials, the selection of appropriate foaming agent types, and a suitable sintering preparation method to produce foamed ceramics with excellent performance, which is of great significance for promoting the comprehensive utilization of solid waste, improving environmental quality, and promoting the comprehensive green transformation of social and economic development. Summary of the invention

[0009] The present application provides a foamed ceramic prepared by rare earth blast furnace slag and fly ash and a preparation method thereof, so as to solve the problems of low utilization rate of fly ash solid waste, too many types of additives, high cost of foaming agent, low compressive strength of product and uneven pores in the method of preparing foamed ceramics using solid waste as raw material in the above-mentioned background technology.

[0010] In the first aspect, the present application provides a foamed ceramic prepared by rare earth blast furnace slag and fly ash, which includes the following raw materials by weight: 30-40 parts of rare earth blast furnace slag, 15-25 parts of fly ash, 19-25 parts of crushed silica, 5-15 parts of coal gangue, 9-15 parts of waste glass, 3-5 parts of talc, and 0.05-1 part of silicon carbide.

[0011] The foamed ceramics provided in this application have the following beneficial effects:

[0012] 1) The raw materials used to fire the foamed ceramics in this application are rich in sources, with rare earth blast furnace slag and fly ash accounting for more than 50% of the raw materials, which greatly improves the utilization rate of rare earth blast furnace slag and fly ash. Not only can the rare earth blast furnace slag and fly ash be effectively treated at the same time, but also the high-value-added resource utilization of solid wastes such as coal gangue and crushed silica is realized.

[0013] 2) In this application, common solid waste resources such as waste glass and talcum powder are added to make up for the alkali metal oxides (K 2 O、Na 2 O) to form a stable SiO 2 -Al 2 O 3 -MO (MO stands for CaO and MgO) multi-component system, thus making it possible to prepare foamed ceramics with excellent performance. A certain amount of alkali metal oxides will also reduce the liquid phase formation temperature, reduce the firing temperature of the material, increase the amount of liquid phase formation, and solve the problem of difficult direct sintering caused by the high melting point of rare earth blast furnace slag and the complexity of fly ash composition.

[0014] 3) In this application, the raw material of rare earth blast furnace slag contains a large amount of glass phase, pyroxene and pyroxene, while the raw material of fly ash contains a large amount of aluminosilicate components, mainly mullite and quartz. When the two are sintered at high temperature, the high-temperature melt is thickened, which will increase the melt viscosity and reduce the surface tension. The glass phase can also combine with the free solid waste, which is conducive to firing a foamed ceramic with stable performance.

[0015] 4) In this application, by using coal gangue and a small amount of silicon carbide as foaming agents, not only can the size and distribution of pores be better controlled, so that the difference in pores inside the product is smaller and more evenly distributed, but the cost of the foaming agent can also be reduced, opening up a new way for the resource utilization of coal gangue.

[0016] Optionally, the components introduced into the rare earth blast furnace slag include 10.10-14.00 parts by weight of SiO 2 , 4.30~6.00 parts Al 2 O 3 , 12.20~16.40 parts CaO, 2.50~3.60 parts MgO, 0.13~0.18 parts Fe 2 O 3 , 0.11~0.15 parts K 2 O, 0.16~0.25 parts Na 2 O.

[0017] Optionally, the fly ash introduced comprises 7.11 to 13.50 parts by weight of SiO 2 , 3.85~6.50 parts Al 2 O3 , 1.10~1.85 parts CaO, 0.18~0.30 parts MgO, 1.20~2.05 parts Fe 2 O 3 , 0.11~0.20 parts K 2 O, 0.11~0.20 parts Na 2 O.

[0018] Optionally, the components introduced by the coal gangue include 1.23 to 3.70 parts by weight of SiO 2 , 1.40~4.25 parts Al 2 O 3 , 0.01~0.02 parts of CaO, 0.01~0.02 parts of MgO, 0.02~0.07 parts of Fe 2 O 3 , 0.01~0.02 parts K 2 O, 0.01~0.02 parts Na 2 O.

[0019] Optionally, the components introduced by the waste glass include 6.58-10.90 parts by weight of SiO 2 , 0.06~0.12 parts Al 2 O 3 , 0.76~1.28 parts CaO, 0.45~0.78 parts MgO, 0.01~0.02 parts Fe 2 O 3 , 0.03~0.04 parts K 2 O, 1.26~2.00 parts Na 2 O.

[0020] In a second aspect, the present application provides a method for preparing foamed ceramics by using rare earth blast furnace slag and fly ash, comprising the following steps:

[0021] The coarse material is crushed to a particle size not greater than 200 meshes to obtain crushed material;

[0022] Mix the crushed material and silicon carbide, add water and wet grind for 15-30 minutes to obtain slurry, the water content in the slurry is 30-50wt%;

[0023] The slurry is dried and then ground to obtain a powder;

[0024] Spreading the powder in a mold and pressing it into shape to obtain a molded blank;

[0025] The formed blank is heated and fired to obtain a foamed ceramic;

[0026] The surface density of foamed ceramic is 50~90kg / m 2; The compressive strength of the foamed ceramic material is 5~20MPa, the bending bearing capacity is ≥1.5, and the water absorption rate is ≤12%.

[0027] Optionally, the coarse material includes 30-40 parts of rare earth blast furnace slag, 15-25 parts of fly ash, 19-25 parts of crushed silica, 5-15 parts of coal gangue, 9-15 parts of waste glass, and 3-5 parts of talc powder by weight;

[0028] The amount of silicon carbide added is 0.05~1 part.

[0029] Optionally, the temperature-raising firing comprises the following steps:

[0030] The formed blank is placed in a firing device and heated from room temperature to a first temperature in an air atmosphere, and the heating time is controlled to be 20 to 25 minutes;

[0031] The temperature is raised from the first temperature to the second temperature, the heating time is controlled to be 55-60 minutes, and the temperature is kept at the second temperature for 80-110 minutes;

[0032] The temperature is raised from the second temperature to the third temperature, the heating time is controlled to be 55-60 minutes, and the temperature is kept at the third temperature for 80-100 minutes;

[0033] The temperature is raised from the third temperature to the firing temperature, the heating time is controlled to be 40-60 minutes, and the firing temperature is kept at 10-15 minutes;

[0034] The temperature is naturally cooled from the firing temperature to room temperature.

[0035] Optionally, the first temperature is 400-450°C, the second temperature is 900-950°C, the third temperature is 1000-1060°C, and the sintering temperature is 1100-1200°C.

[0036] Optionally, the powder is pressed at a pressure of 20-40 MPa during pressing.

[0037] When the slurry is dried, the temperature used is 95~105℃, and it is dried to constant weight;

[0038] The particle size of the powder is 300~400 mesh.

[0039] The method of the present application has the following beneficial effects:

[0040] 1) The method of the present application adopts a direct foaming and sintering method to prepare foamed ceramics, which improves the sintering performance of rare earth blast furnace slag, reduces the foaming and sintering costs, shortens the process flow, and makes the production process green and environmentally friendly. In addition, the method is easy to implement, has low energy consumption and low cost.

[0041] 2) The method of the present application reduces the sintering time of the foamed ceramic by controlling the temperature-raising firing procedure, thereby ensuring the excellent performance of the foamed ceramic, and making the foamed ceramic prepared by rare earth blast furnace slag and fly ash meet the requirements of building wall insulation materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0043] Figure 1 The XRD diagram of rare earth blast furnace slag provided in one embodiment of the present application;

[0044] Figure 2 The xrd diagram of coal gangue provided in one embodiment of the present application;

[0045] Figure 3 The XRD diagram of crushed silica provided in one embodiment of the present application;

[0046] Figure 4 The XRD diagram of fly ash provided in one embodiment of the present application;

[0047] Figure 5 The XRD diagram of the foamed ceramic provided in Example 1 of the present application;

[0048] Figure 6 A cut-away cross-sectional view of a foamed ceramic sample provided in Example 1 of the present application;

[0049] Figure 7 A cut-away cross-sectional view of a foamed ceramic sample provided in Comparative Example 1 of the present application;

[0050] Figure 8 A cut-away cross-sectional view of a foamed ceramic sample provided for Comparative Example 2 of the present application;

[0051] Fig. 9 A cut-away cross-sectional view of a foamed ceramic sample provided in Comparative Example 3 of the present application;

[0052] Fig.10 This is a cross-sectional view of the foamed ceramic sample provided in Comparative Example 4 of the present application. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present application.

[0054] In the first aspect, the present application provides a foamed ceramic prepared by rare earth blast furnace slag and fly ash, which includes the following raw materials by weight: 30-40 parts of rare earth blast furnace slag, 15-25 parts of fly ash, 19-25 parts of crushed silica, 5-15 parts of coal gangue, 9-15 parts of waste glass, 3-5 parts of talc, and 0.05-1 part of silicon carbide.

[0055] In this application, combined with the characteristics of rare earth blast furnace slag and fly ash, the high CaO and SiO 2 The high SiO content of fly ash 2 and Al 2 O 3 The content can satisfy the requirements of foamed ceramic SiO 2 -Al 2 O 3 -MO (MO stands for CaO and MgO) system. However, due to the high melting point of rare earth blast furnace slag and the complexity of fly ash composition, it is not easy to sinter directly. Therefore, waste glass and talcum powder are added to these two raw materials to increase the alkali metal oxide (K 2 O、Na 2 O) content ratio, a certain amount of alkali metal oxides will reduce the liquid phase formation temperature, reduce the sintering temperature of the material, and increase the amount of liquid phase formed, thereby solving the problem of high melting point and difficult sintering.

[0056] The second is the selection of the type of foaming agent. The inorganic foaming agent required for preparing foamed ceramics usually decomposes at high temperature to produce gas, thereby forming pores in the ceramic matrix. The present invention selects coal gangue and a small amount of silicon carbide as the foaming agent for preparing foamed ceramics. Under high temperature conditions, coal gangue has a high ignition loss, which is mainly caused by the evaporation of water in the coal gangue, the volatilization of organic matter, and the generation of gases such as carbon dioxide and sulfide. After repeated sintering experiments, the gas generated by the ignition of coal gangue can generate pores of foamed ceramics. However, due to the complexity of the composition of coal gangue and the presence of other volatile substances in the ignition loss, a small amount of small-sized closed pores are generated when it is used alone as a foaming agent. It is difficult to control the pore size and distribution of foamed ceramics during the sintering process. On this basis, a small amount of silicon carbide needs to be added. The combination of the two as a foaming agent can better control the pore size and distribution, make the pore size appropriate and evenly distributed, and reduce the cost of the foaming agent.

[0057] SiC reacts with oxygen at high temperatures to produce a complex chemical reaction, and the gases produced are related to the reaction temperature and oxygen partial pressure. SiC begins to react at around 900°C to produce CO 2 The gas foaming effect is closely related to the amount of SiC added, particle size, firing temperature, holding time and raw material properties. If the amount is too little, the foaming effect will not be achieved; if it is too much, the dispersion will be uneven and it will be easy to aggregate, resulting in uneven pores and through holes in the foamed ceramic. SiC is an important industrial raw material, so excessive addition will also increase production costs. Increasing the amount of SiC added helps to reduce the high-temperature liquid phase viscosity of the green body and increase gas production, which ultimately leads to an increase in porosity.

[0058] The foamed ceramics provided in this application have the following beneficial effects:

[0059] 1) The raw materials used to fire the foamed ceramics in this application are rich in sources, with rare earth blast furnace slag and fly ash accounting for more than 50% of the raw materials, which greatly improves the utilization rate of rare earth blast furnace slag and fly ash. Not only can the rare earth blast furnace slag and fly ash be effectively treated at the same time, but also the high-value-added resource utilization of solid wastes such as coal gangue and crushed silica is realized.

[0060] 2) In this application, common solid waste resources such as waste glass and talcum powder are added to make up for the alkali metal oxides (K 2 O、Na 2 O) to form a stable SiO 2 -Al 2 O 3 -MO (MO stands for CaO and MgO) multi-component system, thus making it possible to prepare foamed ceramics with excellent performance. A certain amount of alkali metal oxides will also reduce the liquid phase formation temperature, reduce the firing temperature of the material, increase the amount of liquid phase formation, and solve the problem of difficult direct sintering caused by the high melting point of rare earth blast furnace slag and the complexity of fly ash composition.

[0061] 3) In this application, the rare earth blast furnace slag raw material contains a large amount of glass, pyroxene and pyroxene, while the fly ash raw material contains a large amount of aluminosilicate components, mainly mullite and quartz. When the two are sintered at high temperature, the high-temperature melt is thickened, which will increase the melt viscosity and reduce the surface tension. The glass phase can also combine with the free solid waste, which is conducive to firing a foamed ceramic with stable performance.

[0062] 4) In this application, by using coal gangue and a small amount of silicon carbide as foaming agents, not only can the size and distribution of pores be better controlled, so that the difference in pores inside the product is smaller and more evenly distributed, but the cost of the foaming agent can also be reduced, opening up a new way for the resource utilization of coal gangue.

[0063] Optionally, the components introduced into the rare earth blast furnace slag include 10.10-14.00 parts by weight of SiO 2 , 4.30~6.00 parts Al 2 O 3 , 12.20~16.40 parts CaO, 2.50~3.60 parts MgO, 0.13~0.18 parts Fe 2 O 3 , 0.11~0.15 parts K 2 O, 0.16~0.25 parts Na 2 O.

[0064] In the present application, the components introduced into the above rare earth blast furnace slag are calculated based on 30 to 40 parts by weight of rare earth blast furnace slag.

[0065] Optionally, the fly ash introduced comprises 7.11 to 13.50 parts by weight of SiO 2 , 3.85~6.50 parts Al 2 O 3 , 1.10~1.85 parts CaO, 0.18~0.30 parts MgO, 1.20~2.05 parts Fe 2 O 3 , 0.11~0.20 parts K 2 O, 0.11~0.20 parts Na 2 O.

[0066] In the present application, the components introduced into the above fly ash are calculated based on 15-25 parts by weight of fly ash.

[0067] In the present application, the sodium oxide and potassium oxide in the fly ash have excellent fluxing effect and can promote the formation of glass phase; magnesium oxide and calcium oxide belong to alkaline earth metal oxides, which not only have fluxing effect, but also contribute to the formation of crystal phase and improve compressive strength; iron oxide can undergo decomposition reaction under high temperature conditions to release oxygen, regulate the reaction rate of the foaming agent, and at the same time, Fe 3+ Reduced to Fe 2+ , Fe 2+ It has a fluxing effect and can also promote the formation of glass phase.

[0068] Optionally, the components introduced by the coal gangue include 1.23 to 3.70 parts by weight of SiO 2 , 1.40~4.25 parts Al 2 O 3 , 0.01~0.02 parts of CaO, 0.01~0.02 parts of MgO, 0.02~0.07 parts of Fe 2 O 3 , 0.01~0.02 parts K 2O, 0.01~0.02 parts Na 2 O.

[0069] In the present application, the components introduced into the above-mentioned coal gangue are calculated based on 5 to 15 parts by weight of the coal gangue.

[0070] In this application, coal gangue is added to the raw materials as a foaming agent because coal gangue contains residual carbon, which can react with oxygen at high temperature to produce CO and CO 2 Thereby achieving the effect of foaming and forming pores.

[0071] Optionally, the components introduced by the waste glass include 6.58-10.90 parts by weight of SiO 2 , 0.06~0.12 parts Al 2 O 3 , 0.76~1.28 parts CaO, 0.45~0.78 parts MgO, 0.01~0.02 parts Fe 2 O 3 , 0.03~0.04 parts K 2 O, 1.26~2.00 parts Na 2 O.

[0072] In the present application, the components introduced from the above waste glass are calculated based on 9 to 15 parts by weight of waste glass.

[0073] In the present application, the components introduced by every 19 to 28 parts by weight of crushed silica include 18.90 to 25.00 parts of SiO 2 , 0.24~0.35 parts Al 2 O 3 , 0.01~0.02 parts of CaO, 0.01~0.02 parts of MgO, 0.08~0.13 parts of Fe 2 O 3 , 0.05~0.07 parts K 2 O, 0.01~0.02 parts Na 2 O.

[0074] Because SiC will produce a dense layer of SiO on its surface at high temperature 2 The protective layer prevents the further oxidation of SiC in the protective layer. At the same time, the basic oxides and alkali metal oxides (Na 2 O, K 2 O, CaO, MgO, etc.), for SiO 2 The protective layer has a certain corrosive effect, exposing the SiC in the protective layer and promoting the oxidation and foaming of SiC.

[0075] In a second aspect, the present application provides a method for preparing foamed ceramics by using rare earth blast furnace slag and fly ash, comprising the following steps:

[0076] The coarse material is crushed to a particle size not greater than 200 meshes to obtain crushed material;

[0077] Mix the crushed material and silicon carbide, add water and wet grind for 15-30 minutes to obtain slurry, the water content in the slurry is 30-50wt%;

[0078] The slurry is dried and then ground to obtain a powder;

[0079] Spreading the powder in a mold and pressing it into shape to obtain a molded blank;

[0080] The formed blank is heated and fired to obtain a foamed ceramic;

[0081] The surface density of foamed ceramic is 50~90kg / m 2 ; The compressive strength of the foamed ceramic material is 5~20MPa, the bending bearing capacity is ≥1.5, and the water absorption rate is ≤12%.

[0082] In the present application, ball milling is used for grinding in the wet grinding process, and the mass ratio of the mixed material formed by the crushed material and silicon carbide to the grinding ball is 1:3.

[0083] In the present application, wet grinding can make the various components in the raw materials blend better, and due to the presence of water during the wet grinding process, a small amount of each component in the raw materials will dissolve in water, and ball milling allows the molecules in different components to blend with each other, which is beneficial to the distribution of each material in the system.

[0084] The grinding of the slurry after drying can be carried out by ball milling, rod milling, extrusion crushing and other methods. In this application, ball milling is used because the slurry will clump after drying, and the clumped material can be broken up by grinding. Furthermore, by secondary grinding and crushing of the material, the components in the raw material can be distributed secondary, further improving the dispersion of each material. And because some materials will blend and interlock under the action of water during the wet grinding process, the temperature will increase during the drying process, making the materials interlock and arrange more closely, and even forming a cross-linked body or a crystal phase transition. The cross-linked body formed during the drying process can be redispersed through secondary grinding, which will enable a more stable multi-element cross-linked system to be formed during the later firing process, such as the formation of a stable SiO 2 -Al 2 O 3 -MO (MO stands for CaO and MgO) system.

[0085] The method of the present application adopts a direct foaming and sintering method to prepare foamed ceramics, which improves the sintering performance of rare earth blast furnace slag, reduces the foaming and sintering costs, shortens the process flow, and makes the production process green and environmentally friendly. The method is easy to implement, has low energy consumption and low cost.

[0086] Optionally, the coarse material includes 30-40 parts of rare earth blast furnace slag, 15-25 parts of fly ash, 19-25 parts of crushed silica, 5-15 parts of coal gangue, 9-15 parts of waste glass, and 3-5 parts of talc powder by weight;

[0087] The amount of silicon carbide added is 0.05~1 part.

[0088] In this application, the raw materials include coarse materials and silicon carbide, and the particle size of the materials included should be less than 5 mm to facilitate subsequent crushing and grinding. In this application, the XRD diagrams of rare earth blast furnace slag, coal gangue, crushed silica, and fly ash are as follows: Figure 1~Figure 4 As shown, the XRD diagram shows the specific crystal phases contained in the above four materials.

[0089] Optionally, the temperature-raising firing comprises the following steps:

[0090] The formed blank is placed in a firing device and heated from room temperature to a first temperature in an air atmosphere, and the heating time is controlled to be 20 to 25 minutes;

[0091] The temperature is raised from the first temperature to the second temperature, the heating time is controlled to be 55-60 minutes, and the temperature is kept at the second temperature for 80-110 minutes;

[0092] The temperature is raised from the second temperature to the third temperature, the heating time is controlled to be 55-60 minutes, and the temperature is kept at the third temperature for 80-100 minutes;

[0093] The temperature is raised from the third temperature to the firing temperature, the heating time is controlled to be 40-60 minutes, and the firing temperature is kept at 10-15 minutes;

[0094] The temperature is naturally cooled from the firing temperature to room temperature.

[0095] In the present application, the above-mentioned heating process is a uniform heating process to avoid sudden temperature changes that may have adverse effects on the fired ceramics.

[0096] The method of the present application reduces the sintering time of the foamed ceramic by controlling the temperature-raising firing procedure, thereby ensuring the excellent performance of the foamed ceramic, and making the foamed ceramic prepared by rare earth blast furnace slag and fly ash meet the requirements of building wall insulation materials.

[0097] Optionally, the first temperature is 400-450°C, the second temperature is 900-950°C, the third temperature is 1000-1060°C, and the sintering temperature is 1100-1200°C.

[0098] In the present application, the first temperature is 400~450℃. During this process, the bound water in the material is lost, the waste glass begins to undergo phase change, and the material begins to soften; the temperature continues to rise to the second temperature. During this process, the foaming agent coal gangue and silicon carbide begin to react with oxygen to produce gas, and at the same time, other high melting point components in the material begin to undergo phase change, or crystal phase transformation; the temperature further rises to the third temperature, the reaction of the foaming agent to produce bubbles is further intensified, most of the materials undergo phase change and fuse into a new crystal phase, and the gas produced by the foaming agent forms many pores inside the system, and the system expands due to the gas production of the foaming agent; when the temperature is further increased to the firing temperature, the materials in the system are finally fused, and the bubbles produced by the foaming agent can not only play a role in causing pores, but also stir and mix the melted and fused materials. In this process, the materials are more fully fused, and the foaming agent reacts most violently at this stage, producing a large amount of gas. Although the foaming agent produces a large amount of gas, due to the high pressure used during pressing, the materials are tightly compacted. During the firing process, the bubbles produced by the foaming agent will be limited to a certain range to prevent small bubbles from merging into large bubbles, causing the volume of the produced ceramic to expand excessively, thereby affecting its strength.

[0099] Optionally, the powder is pressed at a pressure of 20-40 MPa during pressing.

[0100] When the slurry is dried, the temperature used is 95~105℃, and it is dried to constant weight;

[0101] The particle size of the powder is 300~400 mesh.

[0102] In the present application, the powder is pressed at a pressure of 20~40MPa, which can make the materials in the raw materials squeezed more tightly, which will improve the compatibility of the materials after melting at high temperature during the later firing. Moreover, since the materials are tightly pressed, the pores produced by the foaming agent will be more uniform.

[0103] In the present application, when the slurry is dried, the temperature is raised to a preset drying temperature at a rate of 3-5°C / min. Example

[0104] Example 1

[0105] A foamed ceramic is prepared according to the following method:

[0106] S101. Weigh 30.1 parts of rare earth blast furnace slag, 23.3 parts of fly ash, 24.3 parts of crushed silica, 5.8 parts of coal gangue, 12.6 parts of waste glass and 3.9 parts of talc powder by weight, add them into a ball mill, and ball-mill them until they pass a 200-mesh sieve to obtain crushed material.

[0107] The mass of various chemical components brought into the mixture by 30.1 parts of rare earth blast furnace slag (by weight): 10.10 parts of SiO 2 , 4.30 parts Al 2 O 3 , 12.20 parts CaO, 2.50 parts MgO, 0.13 parts Fe 2 O 3 , 0.11 parts K 2 O, 0.16 parts Na 2 O.

[0108] The mass of various chemical components brought into the mixture by 23.3 parts of fly ash (by weight): 11.76 parts of SiO 2 , 5.95 parts Al 2 O 3 , 1.73 parts CaO, 0.22 parts MgO, 1.83 parts Fe 2 O 3 , 0.18 parts K 2 O, 0.17 parts Na 2 O.

[0109] The mass of various chemical components brought into the mixture by 24.3 parts of crushed silica (by weight): 24.21 parts SiO 2 , 0.34 parts Al 2 O 3 , 0.02 parts CaO, 0.02 parts MgO, 0.13 parts Fe 2 O 3 , 0.07 parts K 2 O, 0.02 parts Na 2 O.

[0110] The mass of various chemical components brought into the mixture by 5.8 parts of coal gangue (by weight): 1.53 parts of SiO 2 , 1.61 parts Al 2 O 3 , 0.01 parts CaO, 0.01 parts MgO, 0.02 parts Fe 2 O 3 , 0.01 parts K 2 O, 0.01 part Na 2 O.

[0111] The mass of various chemical components brought into the mixture by 12.6 parts of waste glass (by weight): 9.30 parts SiO2 , 0.11 parts Al 2 O 3 , 1.09 parts CaO, 0.65 parts MgO, 0.15 parts Fe 2 O 3 , 0.37 parts K 2 O, 1.70 parts Na 2 O.

[0112] The mass of various chemical components brought into the mixture by 3.9 parts of talc (by weight): 0.97 parts SiO 2 , 0.05 parts Al 2 O 3 , 2.18 parts CaO, 0.59 parts MgO, 0.02 parts Fe 2 O 3 , 0.01 parts K 2 O, 0.01 part Na 2 O.

[0113] S102. Add 0.1 parts of silicon carbide and water to the crushed material, and wet grind for 30 minutes to obtain a slurry, wherein the mass ratio of the mixed material obtained after the crushed material and silicon carbide are mixed to the grinding balls is 1:3, the ball mill speed is 120 rpm, the mass proportion of water in the slurry is 40%, and the particle size of the slurry can pass through a 300-400 mesh sieve.

[0114] S103, drying the slurry at 95°C to constant weight, and then ball milling (the mass ratio of material to grinding ball is 1:3, and the ball milling speed is 120 rpm) to obtain a powder with a particle size of 300-400 mesh.

[0115] S104, spreading the powder in a mold, and pressing and molding at a pressure of 30 MPa to obtain a molded blank.

[0116] S105, heating and firing the formed blank to obtain a foamed ceramic;

[0117] During the heating process, the formed blank is placed in a firing device and heated from room temperature to 400°C in an air atmosphere, and the heating time is controlled to be 20 minutes;

[0118] The temperature was raised from 400°C to 900°C, the heating time was controlled to be 60 minutes, and the temperature was kept for 90 minutes;

[0119] Raise the temperature from 900°C to 1060°C, control the heating time to 60 minutes, and keep it at this temperature for 90 minutes;

[0120] Raise the temperature from 1060℃ to 1170~1175℃, control the heating time to 40~60min, and keep it warm for 10min;

[0121] Then cool naturally to room temperature.

[0122] Example 2

[0123] A foamed ceramic is prepared according to the following method:

[0124] S201, weigh 31.1 parts of rare earth blast furnace slag, 24.3 parts of fly ash, 19.4 parts of crushed silica, 10.7 parts of coal gangue, 9.7 parts of waste glass and 4.8 parts of talc powder by weight, add them into a ball mill and ball grind them until they pass through a 200-mesh sieve to obtain a crushed material. The content of the chemical components contained in each component in the above crushed material can be converted with reference to Example 1, which will not be repeated here.

[0125] S202. Add 0.05 parts of silicon carbide and water to the crushed material, and wet grind for 30 minutes to obtain a slurry, wherein the mass ratio of the mixed material obtained after the crushed material and silicon carbide are mixed to the grinding balls is 1:3, the ball mill speed is 120 rpm, the mass proportion of water in the slurry is 30%, and the particle size of the slurry can pass through a 300-400 mesh sieve.

[0126] S203, drying the slurry at 100°C to constant weight, and then ball milling (the mass ratio of material to grinding balls is 1:3, and the ball milling speed is 120 rpm) to obtain a powder with a particle size of 300-400 mesh.

[0127] S204, spreading the powder in a mold, and pressing and molding at a pressure of 30 MPa to obtain a molded blank.

[0128] S205, heating and firing the formed blank to obtain a foamed ceramic;

[0129] During the heating process, the formed blank is placed in a firing device and heated from room temperature to 400°C in an air atmosphere, and the heating time is controlled to be 20 minutes;

[0130] The temperature was raised from 400°C to 900°C, the heating time was controlled to be 60 minutes, and the temperature was kept for 90 minutes;

[0131] Raise the temperature from 900°C to 1060°C, control the heating time to 60 minutes, and keep it at this temperature for 90 minutes;

[0132] Raise the temperature from 1060°C to 1175~1180°C, control the heating time to 46~52min, and keep it warm for 10min;

[0133] Then cool naturally to room temperature.

[0134] Example 3

[0135] A foamed ceramic is prepared according to the following method:

[0136] S301, weigh 33 parts of rare earth blast furnace slag, 19.4 parts of fly ash, 19.4 parts of crushed silica, 13.7 parts of coal gangue, 9.7 parts of waste glass and 4.8 parts of talc powder by weight, add them into a ball mill and ball grind them until they pass through a 200-mesh sieve to obtain a crushed material. The content of the chemical components contained in each component in the above crushed material can be converted with reference to Example 1, which will not be repeated here.

[0137] S302, adding 0.5 parts of silicon carbide and water to the crushed material, and wet grinding for 30 minutes to obtain slurry, wherein the mass ratio of the mixed material obtained after the crushed material and silicon carbide are mixed to the grinding balls is 1:3, the ball mill speed is 100rpm, the mass proportion of water in the slurry is 50%, and the particle size of the slurry can pass through a 300-400 mesh sieve.

[0138] S303, drying the slurry at 105°C to constant weight, and then ball milling (the mass ratio of material to grinding ball is 1:3, and the ball milling speed is 100 rpm) to obtain a powder with a particle size of 300-400 mesh.

[0139] S304, spreading the powder in a mold, and pressing and molding at a pressure of 20 MPa to obtain a molded blank.

[0140] S305, heating and firing the formed blank to obtain foamed ceramics;

[0141] During the heating process, the formed blank is placed in a firing device and heated from room temperature to 400-450°C in an air atmosphere, and the heating time is controlled to be 20-25 minutes;

[0142] The temperature was raised from 400°C to 900°C, the heating time was controlled to be 60 minutes, and the temperature was kept for 90 minutes;

[0143] Raise the temperature from 900°C to 1060°C, control the heating time to 60 minutes, and keep it at this temperature for 90 minutes;

[0144] Raise the temperature from 1060°C to 1175~1180°C, control the heating time to 46~52min, and keep it warm for 10min;

[0145] Then cool naturally to room temperature.

[0146] Example 4

[0147] A foamed ceramic is prepared according to the following method:

[0148] S401, weigh 35 parts of rare earth blast furnace slag, 15.5 parts of fly ash, 24.3 parts of crushed silica, 5.8 parts of coal gangue, 14.6 parts of waste glass and 4.8 parts of talc powder by weight, add them into a ball mill and ball grind them until they pass through a 200-mesh sieve to obtain a crushed material. The content of the chemical components contained in each component in the above crushed material can be converted with reference to Example 1, which will not be repeated here.

[0149] S402, adding 0.35 parts of silicon carbide and water to the crushed material, wet grinding for 30 minutes, to obtain slurry, wherein the mass ratio of the mixed material obtained after the crushed material and silicon carbide are mixed to the grinding balls is 1:3, the ball mill speed is 80rpm, the mass proportion of water in the slurry is 30%, and the particle size of the slurry can pass through a 300-400 mesh sieve.

[0150] S403, drying the slurry at 100°C to constant weight, and then ball milling (the mass ratio of material to grinding ball is 1:3, and the ball milling speed is 80 rpm) to obtain a powder with a particle size of 300-400 mesh.

[0151] S404, spreading the powder in a mold, and pressing and molding at a pressure of 40 MPa to obtain a molded blank.

[0152] S405, heating and firing the formed blank to obtain a foamed ceramic;

[0153] During the heating process, the formed blank is placed in a firing device and heated from room temperature to 400°C in an air atmosphere, and the heating time is controlled to be 20 minutes;

[0154] The temperature was raised from 400°C to 900°C, the heating time was controlled to be 60 minutes, and the temperature was kept for 90 minutes;

[0155] Raise the temperature from 900°C to 1060°C, control the heating time to 60 minutes, and keep it at this temperature for 90 minutes;

[0156] Raise the temperature from 1060℃ to 1180~1185℃, control the heating time to 50~55min, and keep it warm for 10min;

[0157] Then cool naturally to room temperature.

[0158] Example 5

[0159] A foamed ceramic is prepared according to the following method:

[0160] The remaining operations are the same as those in Example 2, except that the raw materials include the following materials in parts by weight: 31.1 parts of rare earth blast furnace slag, 20.4 parts of fly ash, 21.3 parts of crushed silica, 11.7 parts of coal gangue, 11.6 parts of waste glass and 3.9 parts of talc.

[0161] Example 6

[0162] A foamed ceramic is prepared according to the following method:

[0163] The remaining operations are the same as those of Example 2, except that the raw materials include the following materials by weight: 39.8 parts of rare earth blast furnace slag, 17.4 parts of fly ash, 22.3 parts of crushed silica, 6.7 parts of coal gangue, 11.6 parts of waste glass and 3.9 parts of talc. The amount of silicon carbide added is 1 part by weight.

[0164] Comparative Example 1

[0165] The remaining operations are the same as in Example 1, except that the amount of silicon carbide added to the raw material is 1.3 parts by weight.

[0166] Comparative Example 2

[0167] The remaining operations are the same as those in Example 1, except that silicon carbide is not added to the raw materials.

[0168] Comparative Example 3

[0169] The remaining operations are the same as those in Example 1, except that the pressure used when the powder is pressed in the mold is 10 MPa.

[0170] Comparative Example 4

[0171] The remaining operations are the same as those in Example 1, except that the pressure used when the powder is pressed in the mold is 50 MPa.

[0172] Experimental example

[0173] 1. The foamed ceramics prepared by the methods of Examples 1 to 6 and Comparative Examples 1 to 4 were measured for area density, compressive strength, flexural bearing capacity and water absorption according to the method in GB / T23450-2009 "Thermal insulation strips for building partition walls". The measurement results are shown in Table 1.

[0174] Table 1:

[0175]

[0176] It can be seen from the data in Table 1 that when the amount of silicon carbide added to the raw material is high, that is, 1.3 parts in Comparative Example 1, the area density and compressive strength of the fired foamed ceramic are both low, and its water absorption rate is also high at 18%, which is lower than the limit value specified in the standard GB / T23450-2009. This shows that excessive silicon carbide will affect the strength of the foamed ceramic, and too much foaming agent, that is, silicon carbide, will increase the surface porosity of the fired foamed ceramic, resulting in a high water absorption rate. This also shows that the addition of excessive silicon carbide will have an adverse effect on the fired foamed ceramic.

[0177] When silicon carbide is not added to the raw materials, that is, the data of Comparative Example 2, although the fired foamed ceramic has a high compressive strength, its area density is too large and does not meet the standards of corresponding building materials. In other words, too low an amount of silicon carbide added will also have adverse consequences on the foamed ceramic.

[0178] When the pressing pressure in the mold is too small, which is the result of comparative example 3, it will lead to the result similar to that of excessive addition of foaming agent, that is, the foamed ceramic is over-foamed, resulting in low area density and compressive strength, and high water absorption.

[0179] When the pressing pressure in the mold is too high, which is the result of Comparative Example 5, the pores inside the foamed ceramic are too small and the foaming is insufficient, which is the result that the area density of the foamed ceramic is too high.

[0180] 2. The foamed ceramic obtained by firing in Example 1 was subjected to X-ray diffraction analysis, and its XRD pattern was as follows: Figure 5 As shown, through Figure 5 It can be seen that the main crystal phases in the fired foamed ceramics are diopside phase and quartz phase.

[0181] 3. The foamed ceramics fired in the above-mentioned Example 1 and Comparative Examples 1 to Comparative Examples 4 are cut to display their internal structures. Since the internal structures of the products fired in each embodiment are similar, the foamed ceramic of Example 1 in the embodiment is selected for display. The results are as follows: Figure 6~Figure 9 shown.

[0182] pass Figure 6~Figure 9 It can be seen from the display pictures that the physical properties of the fired foamed ceramics are basically consistent with the measured data in Table 1.

[0183] Example 1 (i.e. Figure 6 The foamed ceramics (shown in the figure) have evenly distributed pores inside, relatively uniform pore sizes, and a smooth ceramic surface.

[0184] Comparative Example 1 (i.e. Figure 7 The foamed ceramics shown in the figure have mostly large pores inside, an uneven surface, and some pores close to the surface are open.

[0185] Comparative Example 2 (i.e. Figure 8 The foamed ceramics (shown in Figure 1) have basically small bubbles distributed inside and the overall structure is relatively dense.

[0186] Comparative Example 3 (i.e. Fig. 9 The foamed ceramics (shown in Figure 2) have uneven pore sizes, a large number of large pores, and a relatively loose overall structure.

[0187] Comparative Example 4 (i.e. Fig.10The foamed ceramics shown in the figure have many small bubbles inside. Figure 8 As a result, there are relatively more bubbles, but the overall appearance of the sample is relatively dense.

[0188] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing foamed ceramics by using rare earth blast furnace slag and fly ash, characterized in that: The steps include: The coarse material is crushed to a particle size not greater than 200 meshes to obtain crushed material; Mix the crushed material and silicon carbide, add water and wet grind for 15-30 minutes to obtain slurry, the water content in the slurry is 30-50wt%; The slurry is dried and then ground to obtain a powder; Spreading the powder in a mold and pressing it into shape to obtain a molded blank; The formed blank is heated and fired to obtain a foamed ceramic; The coarse material comprises, by weight, 30-40 parts of rare earth blast furnace slag, 15-25 parts of fly ash, 19-25 parts of crushed silica, 5-15 parts of coal gangue, 9-15 parts of waste glass, and 3-5 parts of talc; The amount of silicon carbide added is 0.05~1 part The formed blank is placed in a firing device and heated from room temperature to a first temperature in an air atmosphere, and the heating time is controlled to be 20 to 25 minutes; The temperature is raised from the first temperature to the second temperature, the heating time is controlled to be 55-60 minutes, and the temperature is kept at the second temperature for 80-110 minutes; The temperature is raised from the second temperature to the third temperature, the heating time is controlled to be 55-60 minutes, and the temperature is kept at the third temperature for 80-100 minutes; The temperature is raised from the third temperature to the firing temperature, the heating time is controlled to be 40-60 minutes, and the firing temperature is kept at 10-15 minutes; The temperature is naturally cooled from the firing temperature to room temperature; The first temperature is 400-450°C, the second temperature is 900-950°C, the third temperature is 1000-1060°C, and the sintering temperature is 1100-1200°C; When the powder is pressed into shape, a pressure of 20~40MPa is used for pressing; The slurry is dried at a temperature of 95-105°C until constant weight is achieved.

2. The method for preparing foamed ceramics by using rare earth blast furnace slag and fly ash according to claim 1, characterized in that: The surface density of the foamed ceramic is 50-90 kg / m 2 ; The compressive strength of the foamed ceramic material is 5~20MPa, and the water absorption rate is ≤12%.

3. The method for preparing foamed ceramics by using rare earth blast furnace slag and fly ash according to claim 1, characterized in that: The particle size of the powder is 300~400 mesh.

4. The method for preparing foamed ceramics by using rare earth blast furnace slag and fly ash according to claim 1, characterized in that: The components introduced into the rare earth blast furnace slag include, by weight, 10.10-14.00 parts of SiO2, 4.30-6.00 parts of Al2O3, 12.20-16.40 parts of CaO, 2.50-3.60 parts of MgO, 0.13-0.18 parts of Fe2O3, 0.11-0.15 parts of K2O, and 0.16-0.25 parts of Na2O.

5. The method for preparing foamed ceramics by using rare earth blast furnace slag and fly ash according to claim 1, characterized in that: The components introduced into the fly ash include, by weight, 7.11-13.50 parts of SiO2, 3.85-6.50 parts of Al2O3, 1.10-1.85 parts of CaO, 0.18-0.30 parts of MgO, 1.20-2.05 parts of Fe2O3, 0.11-0.20 parts of K2O, and 0.11-0.20 parts of Na2O.

6. The method for preparing foamed ceramics by using rare earth blast furnace slag and fly ash according to claim 1, characterized in that: The components introduced by the coal gangue include, by weight, 1.23-3.70 parts of SiO2, 1.40-4.25 parts of Al2O3, 0.01-0.02 parts of CaO, 0.01-0.02 parts of MgO, 0.02-0.07 parts of Fe2O3, 0.01-0.02 parts of K2O, and 0.01-0.02 parts of Na2O.

7. The method for preparing foamed ceramics by using rare earth blast furnace slag and fly ash according to claim 1, characterized in that: The components introduced from the waste glass include, by weight, 6.58-10.90 parts of SiO2, 0.06-0.12 parts of Al2O3, 0.76-1.28 parts of CaO, 0.45-0.78 parts of MgO, 0.01-0.02 parts of Fe2O3, 0.03-0.04 parts of K2O, and 1.26-2.00 parts of Na2O.

Citation Information

Patent Citations

  • Method for preparing foaming ceramic materials from blast-furnace slags and high-aluminum pulverized coal ash

    CN108503371A

  • Preparation method of foamed ceramic thermal insulation material as well as product thereof

    CN103553701A

  • Manufacturing method of foamed ceramic plate

    CN114671701A